2009
DOI: 10.1128/mcb.00654-09
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Lim Protein Interacts with Cofilin 2 and Regulates F-Actin Dynamics in Cardiac and Skeletal Muscle

Abstract: The muscle LIM protein (MLP) and cofilin 2 (CFL2) are important regulators of striated myocyte function. Mutations in the corresponding genes have been directly associated with severe human cardiac and skeletal myopathies, and aberrant expression patterns have often been observed in affected muscles. Herein, we have investigated whether MLP and CFL2 are involved in common molecular mechanisms, which would promote our understanding of disease pathogenesis. We have shown for the first time, using a range of bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 89 publications
1
68
1
3
Order By: Relevance
“…S4B and C). In contrast to the findings of Papalouka et al (44), who reported that at specific MLP/cofilin ratios MLP enhances CFL2 depolymerizing activity, our data support that CFL2 and MLP have opposite effects on AF dynamics irrespective of their relative concentrations.…”
Section: Resultscontrasting
confidence: 94%
See 2 more Smart Citations
“…S4B and C). In contrast to the findings of Papalouka et al (44), who reported that at specific MLP/cofilin ratios MLP enhances CFL2 depolymerizing activity, our data support that CFL2 and MLP have opposite effects on AF dynamics irrespective of their relative concentrations.…”
Section: Resultscontrasting
confidence: 94%
“…In addition, MLP-GFP colocalized with ␣-ac- tinin in nascent myofibrils (Fig. 3D to G), an observation that is well consistent with the previously reported localization of endogenous MLP at the Z line of muscle cells (18,24,44,47). In support of MLP also functioning as an actin cross-linker/stabilizer in differentiated muscle cells/tissues, MLP-GFP-expressing HL-1 cells frequently exhibited more prominent actin-based structures than the surrounding nontransfected cells (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…CFL2 is a muscle-specific protein that belongs to the actin depolymerization factor/cofilin family; it regulates actin dynamics by promoting actin filament turnover (51,53). CFL2 binds actin; phosphorylation prevents actin binding (7).…”
Section: Cfl2mentioning
confidence: 99%
“…60 DFD meat occurs when the ultimate pH post-mortem measured after 12- 48 61 hours is higher than 6.0 [8]. The elevated pH is associated with relatively little 62 denaturation of proteins, water is tightly bound and little or no exudates are expelled 63 [6].…”
Section: Introduction 47mentioning
confidence: 99%